2019
DOI: 10.1097/jom.0000000000001541
|View full text |Cite
|
Sign up to set email alerts
|

Shiftwork and Biomarkers of Subclinical Cardiovascular Disease

Abstract: Objective: To assess the association of shift work with biomarkers of subclinical cardiovascular disease and examine the moderating role of body mass index (BMI) in a police cohort.Methods: A cross-sectional analysis was conducted among officers who were categorized as working the day, evening, or night shift. Comparisons with inflammatory biomarkers were performed among shifts using analysis of variance/covariance and further stratified by BMI to assess potential effect modification. Results:Associations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
(64 reference statements)
0
3
0
1
Order By: Relevance
“…Male officers who worked afternoon or night shifts had larger declines in endothelial function compared to officers working day shift 135 . Another study found that officers working night shift had higher levels of biomarkers for subclinical CVD (leukocytes, TNF‐α, and homocysteine) compared to officers working day shift 149 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Male officers who worked afternoon or night shifts had larger declines in endothelial function compared to officers working day shift 135 . Another study found that officers working night shift had higher levels of biomarkers for subclinical CVD (leukocytes, TNF‐α, and homocysteine) compared to officers working day shift 149 …”
Section: Resultsmentioning
confidence: 99%
“…135 Another study found that officers working night shift had higher levels of biomarkers for subclinical CVD (leukocytes, TNF-α, and homocysteine) compared to officers working day shift. 149 Few studies described mitigation strategies for chronic diseases.…”
Section: Chronic Diseasementioning
confidence: 99%
“…All eligible studies were published between the periods from 2007 to 2022. Out of these, ten studies were from America,[ 15 17 21 22 23 24 25 26 27 28 ] seven were from Europe,[ 16 29 30 31 32 33 34 ] seven were from East Asia,[ 10 14 35 36 37 38 39 ] and one study was from the Middle East. [ 40 ] Most of the studies were cross-sectional, and only one used a retrospective design.…”
Section: R Esultsmentioning
confidence: 99%
“…In 15 of those studies, the average age of the shift employees was lower than that of the day employees. The study population represented employees from different occupational sectors such as health care,[ 10 16 21 24 28 29 31 32 33 ] manufacturing,[ 14 25 27 36 37 38 39 ] police,[ 22 26 ] universities,[ 35 ] and the general population. [ 23 ] Total WBC counts were reported in 20 studies, while both total and differential WBC counts were reported in eight studies.…”
Section: R Esultsmentioning
confidence: 99%
“…Αντίστροφη ήταν η μεταβολή των επιπέδων της κορτιζόλης στην ίδια ομάδα εργαζομένων. Τέλος, η σχετιζόμενη με την εργασία σε βάρδιες διαταραχή του κιρκάδιου ρυθμού, έχει σχετισθεί με αυξημένη επίπτωση νεοπλασιών, που αποδίδεται στην απορύθμιση του ενδοκρινικού συστήματος και την πυροδότηση ορμονοεξαρτώμενων νεοπλασιών όπως του μαστού [44,47], σακχαρώδους διαβήτη τύπου ΙΙ [48], παχυσαρκίας [49] και καρδιαγγειακών νοσημάτων [50].…”
Section: διαφοροποίηση των κιρκάδιων ρυθμών σε μη παθολογικές καταστάσειςunclassified